Ileocolonic Ulcer Treated by Endoscopic Application of Collagen-Polyvinylpyrrolidone - Andrés de Hoyos Garza; Edgar A Esparza Aguilar; Griselda Checa Richards (Canadian Journal of Gastroenterology)
Ulceration is a complication that may occur after an ileocolonic anastomosis. Most of the etiologies remain speculative. The case of a 33-year-old woman with eosinophilic colitis is reported, in whom a colectomy with an ileocolonic anastomosis was performed. After four months, the patient presented with a stenosis in the ileocolonic anastomosis, necessitating surgical restoration. Four weeks later, the patient presented with rectal bleeding, and a colonoscopy showed an ulcer in the anastomosis. Collagen-polyvinylpyrrolidone was applied into and on the surface of the ulcer, and five days later the procedure was repeated. Follow-up endoscopies at seven days and three months showed complete healing of the ulcer and the patient remained without bleeding throughout a further four weeks of follow-up tests. It was concluded that this biological product could be an excellent treatment for these lesions.